PTH-225 Paediatric malnutrition screening on admission: a comparison of different tools and their association with body composition and clinical outcomes. (22nd June 2015) - Pompa, NE Lara; Williams, J; Macdonald, S; Fawbert, K; Valente, J; Kennedy, K; Shaw, V; Wells, JC; Hill, S; Fewtrell, M
Abstract : Introduction: The aim of the study was to evaluate associations between currently available paediatric malnutrition screening tools (MSTs), baseline body composition (BC) measurements and clinical outcomes (length of stay-LOS; nutrition status on discharge-NS) in children admitted to a tertiary referral hospital. Method: 128 children (mean age 10.7yr; 49.2% male; 54.7% surgical) admitted to Great Ormond Street Hospital (GOSH) under any specialty and expected stay >3 days were enrolled. 3 MSTs (Paediatric Yorkhill Malnutrition Score-PYMS; Screening Tool for the Assessment of Malnutrition in Paediatrics-STAMP; Screening Tool for Risk of Impaired Nutritional Status and Growth-STRONG) were implemented on admission. Weight (WT) and BC measurements (lean (LM) and fat mass (FM) by dual Energy X-ray Absorptiometry) were obtained within 48 h of admission and SD scores (SDS) calculated from UK BC reference data. 1 WT and LOS were recorded on discharge. Results: STAMP classified more patients as high risk (HR) compared to PYMS and STRONG. Most patients were identified as moderate risk (MR) by both STAMP and STRONG, and low risk (LR) by PYMS. STAMP and STRONG classified more surgical patients in HR and MR categories respectively. STAMP and STRONG showed the best agreement (60.9% agreement, 0.427 kappa), followed by STRONG and PYMS (48.4% agreement; 0.321 kappa) and STAMP and PYMS (46.1% agreement; 0.284 kappa). Children classified HR by STRONG had significantly lower WT, LM and FM SDS compared to LR and MR patients. The HR category in STAMP also had significantly lower LM SDS. MSTs did not correlate significantly with LOS and discharge NS (WT change), although there was a tendency for HR patients to stay longer than predicted. Conclusion: STAMP and STRONG seem to show the best agreement, and identify HR patients with abnormal BC (especially low LM). GOSH patients are generally short and have multiple and chronic diagnoses, possibly explaining the proportion of patients classified as LR by PYMS, which used body mass index scores and does not consider underlying diagnosis. Although HR patients showed a tendency for worse clinical outcomes, these were not significant, probably reflecting the limitations of these generic outcomes for this heterogeneous group. Thus, further research is needed in specific patient groups to establish the usefulness of each MST in different conditions. Disclosure of interest: None Declared. Reference: Wells JC et al . AJCN 2012;96:1316–26